7.7k views
1 vote
Please help quickly.

Please help quickly.-example-1
User Mark Jones
by
5.2k points

2 Answers

3 votes
The answer is x= 2, y = 5
User Erik Giberti
by
5.4k points
0 votes

Answer:

x = 2, y = 5

Explanation:

Given the 2 equations

y = - 2x + 9 → (1)

y = 4x - 3 → (2)

Substitute y = 4x - 3 into (1)

4x - 3 = - 2x + 9 ( add 2x to both sides )

6x - 3 = 9 ( add 3 to both sides )

6x = 12 ( divide both sides by 6 )x = 2

Substitute x = 2 into either of the 2 equations and evaluate for y

Substituting into (2)

y = 4(2) - 3 = 8 - 3 = 5

Then x = 2, y = 5

User Blamb
by
5.7k points